Assessment of Mobility and Pain Intensity among Patients with Cervical Discopathy Treated Conservatively at the Neurosurgical Outpatient Clinic - Bąk, Ewelina; Śleziak, Karolina (Journal of Education, Health and Sport, 2018)
IntroductionDiscopathy of the cervical spine is becoming an increasingly common problem among the entire population, assuming the status of a civilization disease.Aim of this paperThe aim of the paper was to assess the functional efficiency and pain intensity among patients treated conservatively due to the degenerative disc disease of the cervical spine. Materials and methodsThe study included 100 patients treated conservatively in the neurosurgical outpatient clinic. A self-prepared questionnaire, the NRS (Numerical Rating Scale) pain scale and the NDI (Neck Disability Index) performance evaluation scale were used to conduct the research.FindingsDifferences in pain severity were found in the respective Neck Disability Index scale groups. There was no significant correlation between the type of work and the degree of disability on the Neck Disability Index scale and the relationship between the mode of work and the perceived pain.ConclusionsOn the basis of the conducted research, it was found that there was a significant relationship between cervical spine pain and the degree of disability defined in the Neck Disability Index. The type of work performed did not show any relationship with the degree of Neck Disability Index disability, and the mode in which the work is performed has no significant impact on pain.